(untitled) (Bangladesh Journal of Scientific Research, 2011)
Key words: Metal-ascorbic acid complex; voltammetry; semi-empirical computation; quantitative estimation Bangladesh J. Sci. Res. 24(1): 1-14, 2011 (June)